SZ_GERICHTE GPR 2017 15 vom 21. November 2017 , Einstellung eines Strafverfahrens (Kosten und Entschädigung) - SZ Gerichte (2017)
Einstellung eines Strafverfahrens (Kosten und Entschädigung) | Wirtschaftl. Nebenfolgen max. Fr. 5\x27000.00